Resilience after Child Abuse and Neglect: A Systematic Review of Protective Factors - Öznur Bayar; Türkan Doğan (Psikoloji Çalışmaları)
Despite their harmful effects on mental health, experiences of child abuse and neglect can be influenced by protective factors that contribute to psychological resilience. This systematic review of protective factors associated with psychological resilience after child abuse and neglect summarizes the methodological quality and general characteristics of selected studies. The PRISMA-P guide and a qualitative assessment control list were used to assess the methodological quality of the studies. Three databases (PubMed, Ulakbim, and Web of Science) were searched in English and Turkish to identify studies published between January 2016 and July 2021. We identified 4094 articles in the initial search. Four additional articles were included using references from these articles. Thirty-nine studies were included based on inclusion and exclusion criteria. The quality of the studies was assessed with the developed control list. Protective factors were classified according to the conceptual foundations of preceding studies that examined resilience after child abuse and neglect using an ecological approach (individual, family/relational, environmental/community). Most of the included research was of moderate quality. The most frequently studied variables consistently found to have a protective role in individuals with a history of child abuse and neglect during young adulthood and adulthood were resilience scores from individual factors and perceived social support from family/relational factors. A limited number of studies addressed the protective role of environmental/community factors. In relatively few studies that focused only on child sexual abuse, the contributions of individual, family/relational, and environmental/community protective factors to resilience were not significant. Based on our results, it is recommended to examine environmental/community factors and consider child sexual abuse separately when investigating protective factors related to resilience in individuals who have experienced child abuse and neglect.